Doctoral Studies in the Context of Global Trends: Problems and Key Factors of Development - M. V. Seroshtan; K. A. Artamonova; G. Z. Akimova; E. V. Berezhnaya; E. V. Seroshtan (Moscow Polytechnic University, 2022)
The article focuses on the analysis of the current state, problems and key factors in the development of Russian doctoral education in connection with its transition from 2022/2023 academic year to the implementation of a new model in the context of global trends. As a result of analyzing and evaluating statistical data for 2010-2021 and summarizing numerous publications of researchers, the authors conclude that the trend of steady decline in the efficiency of doctoral education over the past decade is a systemic problem. It is proved that the transition to a new model of implementation of doctoral training programs for scientific and scientific-pedagogical staff aimed at improving its effectiveness, strengthening the scientific component and the quality of PhD dissertations is an important and necessary condition, but not sufficient to solve the existing problem. This study is an attempt to systematize the factors affecting the development of doctoral education in Russia, which determine the possibility of creating necessary and sufficient conditions for the effective functioning of the system of training highly qualified personnel. The authors identify three groups of key factors: dynamic changes in the development of the state policy aimed at improving management in the field of training scientific and scientific-pedagogical personnel; developed ecosystem of educational and scientific organizations that provide doctoral education, including infrastructure, information, financial, organizational resources and scientific potential; doctoral students with interest and abilities in research activities, possessing a set of competencies necessary for the development of doctoral education. At the same time, such prospective tasks are considered as increasing reputational responsibility of organizations, which offer programs for training scientific and scientific-pedagogical personnel; forming effective system of targeted training in doctoral education; developing mechanisms for integration of science, higher education and industry by means of creating consortiums, the incentives for which are laid down in the "Priority 2030" university state support program.